2008
DOI: 10.1007/s10384-007-0506-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of choroidal neovascularization by blocking vascular endothelial growth factor receptor tyrosine kinase

Abstract: Both Flt-1 and KDR/Flk-1 have a significant role in CNV formation. Suppression of apoptosis may be involved in the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…They concluded that the KDR selective inhibitor might be beneficial for the treatment of intraocular angiogenic diseases. A recent study performed by Kami et al [36] on experimental choroidal neovascularization also showed significance of Flt-1 and KDR/Flk-1 receptor in choroidal neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the KDR selective inhibitor might be beneficial for the treatment of intraocular angiogenic diseases. A recent study performed by Kami et al [36] on experimental choroidal neovascularization also showed significance of Flt-1 and KDR/Flk-1 receptor in choroidal neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Daily i.p. injections of SU5416, a VEGF receptor 2 (VEGFR-2) tyrosine kinase inhibitor (49,50), after corneal alkali burn injury significantly reduced the growth of CD31 + blood vessels at day 7 postinjury, abolishing the difference between control and NC-Foxc1 +/− mice ( Fig. 6 A and B).…”
Section: Increased Angiogenic Response Attributable To Foxc1 Haploinsmentioning
confidence: 99%
“…17,18 Inhibition of VEGF-mediated signaling pathways by blocking VEGFR also suppresses the formation of laser-induced CNV. 10,19,20 SU5416, a novel synthetic compound and an inhibitor of VEGFR-1 and VEGFR-2, suppresses laser-induced CNV in a mouse model, with significant effects produced following both intraperitoneal and intravitreal administration. 10,19 Systematic administration of axitinib, which inhibits receptor tyrosine kinases of VEGFR-1, VEGFR-2, and VEGFR-3, reportedly suppressed and regressed laser-induced CNV.…”
Section: Discussionmentioning
confidence: 99%
“…10,19,20 SU5416, a novel synthetic compound and an inhibitor of VEGFR-1 and VEGFR-2, suppresses laser-induced CNV in a mouse model, with significant effects produced following both intraperitoneal and intravitreal administration. 10,19 Systematic administration of axitinib, which inhibits receptor tyrosine kinases of VEGFR-1, VEGFR-2, and VEGFR-3, reportedly suppressed and regressed laser-induced CNV. 20 Systemically administered DC101, a murine monoclonal antibody against VEGFR-2, also suppressed the formation of CNV.…”
Section: Discussionmentioning
confidence: 99%